Methodology for spectral emissivity measurement by means of single color pyrometer. (March 2016) - Purpura, Carlo; Trifoni, Eduardo; Musto, Marilena; Rotondo, Giuseppe; della Ragione, Roberto
Highlights: Emissivity measurement technique. Provided formula to evaluate the emissivity whatever value was set on the pyrometer. Comparison between experimental and semi empirical formula values. Abstract: The application of non-intrusive optical devices, such as infrared pyrometers able to measure the temperature of surfaces, makes possible the evaluation of emissivity curve of the tested materials at different temperature values. In this paper the authors propose a methodology for the spectral emissivity measurement by means of a single color pyrometer providing a semi-empirical formula, obtained experimentally at CIRA's laboratory. The semi-empirical formula allows to know the actual emissivity value of the sample's surface for whatever emissivity value set up on the pyrometer. The agreement between the experimental emissivity and the emissivity predicted by semi-empirical formula was verified.